The Implementation of Cooperative Learning Model For Critical Thinking Skills in the History Subject at SMA Pekanbaru - Isjoni Isjoni (International Journal of Educational Best Practices, 2017)
In the approach to learning, teachers must be able to create an active, creative, effective, and funlearing. One of the learning approaches that can be used to create this active, creative, effectiveand fun learning in a group is cooperative learning. Jigsaw was particularly selected from varioustypes of cooperative learning. It was because it is used by researchers in science education, andless popular in social science education. Jigsaw arouse students' attitudes to learning, including inthe History subject. Jigsaw that is one ofthe types of cooperative learning models that encouragesstudents to be active and help each others in mastering the subject matter to achieve maximumperformance. The aim of the study was to see the different models of cooperative learning onstudents' critical thinking skills in the History subject. The method used was by using the teststatistics with analysis using Excel for Windows. To determine whether there is any differences,tests of paired data (Student's t-test) were comducted. If there are no significant differencesbetween the dependent variable for the pre-test, it will be used followed by ANOVA in the posttest. The results showed that there is a difference between the type of cooperative learning modeljigsaw with traditional learning in the study on the critical thinking skills of students in the Historysubject.